Evaluating where and how habitat restoration is undertaken for animals. Issue 4 (16th May 2019) - Hale, Robin; Mac Nally, Ralph; Blumstein, Daniel T.; Swearer, Stephen E.
Abstract : Habitat restoration is vital to ameliorate the effects of anthropogenic disturbances on animal habitats. We reviewed the peer‐reviewed literature to examine where and how habitat restoration is undertaken. Our aim was to identify key knowledge gaps as well as research and monitoring needs that can inform future restoration actions. We found: (1) marine and terrestrial actions focus most commonly on restoring vegetation, and freshwater actions focus on restoring the in‐channel habitat; (2) arthropods are the most common focal group; (3) there is often no collection of pre‐restoration data, so certainty in attributing environmental changes to restoration actions is limited; and (4) population and community measures are most commonly used in monitoring programs, which only show if animals are present at restored sites and not whether they are able to grow, survive, and reproduce. We highlight three important considerations for future restoration actions. First, more integration of knowledge among freshwater, marine, and terrestrial systems will help us to understand how, and why, restoration outcomes might vary in different contexts. Second, where possible, restoration projects should be assessed using before‐after‐control‐impact designs, which will provide the strongest evidence if desired restoration responses occur. Third, if the goal of restoration is to develop self‐sustaining breeding populations of target animals, then measures of fitness (i.e. breeding, survival) should be collected. These recommendations will hopefully help guide more effective restoration practices and monitoring in the future.